Комплексная психофармокотерапия дисморфных болевых ощущений у подростков с психическими расстройствами = Integrated psychopharmacotherapy dismorfing pain in adolescents with psychiatric disorders - Chernyshov, O. V. (Journal of Education, Health and Sport, 2015)
Chernyshov O. V. Комплексная психофармокотерапия дисморфных болевых ощущений у подростков с психическими расстройствами = Integrated psychopharmacotherapy dismorfing pain in adolescents with psychiatric disorders. Journal of Education, Health and Sport. 2015;5(8):210-218. ISSN 2391-8306. DOI 10.5281/zenodo.28073 http://dx.doi.org/10.5281/zenodo.28073 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A210-218 https://pbn.nauka.gov.pl/works/607755 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.06.2015. Revised 15.07.2015. Accepted: 12.08.2015. УДК 616.89:612.017.1 КОМПЛЕКСНАЯ ПСИХОФАРМОКОТЕРАПИЯ ДИСМОРФНЫХ БОЛЕВЫХ ОЩУЩЕНИЙ У ПОДРОСТКОВ С ПСИХИЧЕСКИМИ РАССТРОЙСТВАМИ INTEGRATED PSYCHOPHARMACOTHERAPY DISMORFING PAIN IN ADOLESCENTS WITH PSYCHIATRIC DISORDERS О. В. Чернышов O. V. Chernyshov Николаевская областная психиатрическая больница №1 Mykolaiv Regional Psychiatric Hospital № 1 Summary This article presents the theoretical generalization and the new decision of an actual problem of modern psychiatry - the improvement of the treatment of adolescents with dismorfic painful disorders in the structure of mental disorders by implementing a comprehensive program of pharmacotherapy and psychotherapy, developed on the basis of socio-demographic, clinical, psychopathological, pathopsychological characteristics of patients research. Key words: complex psychopharmacotherapy, psychotherapy, dismorfing pain, mental disorders, adolescents. Резюме В данной статье приведены теоретические обобщения и новое решение актуальной задачи современной психиатрии – усовершенствование системы лечения подростков с дисморфными болевыми ощущениями в структуре психических расстройств, путем внедрения программы комплексной психофармакотерапии и психотерапии, разработанной на основании исследования социально-демографических, клинико-психопатологических и патопсихологических характеристик пациентов. Ключевые слова: комплексная психофармакотерапия, психотерапия, дисморфные болевые ощущения, психические расстройства, подростки.